2017
DOI: 10.2196/formative.7257
|View full text |Cite
|
Sign up to set email alerts
|

A Health Professional–Led Synchronous Discussion on Facebook: Descriptive Analysis of Users and Activities

Abstract: Background Arthritis is a major cause of pain and disability. Arthritis New Zealand (Arthritis NZ) is a nongovernmental organization that provides advocacy, information, and advice and support services for people with arthritis in New Zealand. Since many people seek health information on the Web, Arthritis NZ has a webpage and a Facebook page. In addition to static content, Arthritis NZ provides synchronous discussions with an arthritis educator each week via Facebook. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Nonetheless, they underscored that the messages relatives and other patients provided through the network represented significant emotional support 10 . In 2017, a nongovernmental organization that supplies patients in New Zealand with information on arthritis analyzed the features of the interactions through the Facebook page and identified that the comments were meant to seek and offer support, obtain information, or share experiences 21 . In line with these studies, although Facebook was among the most consulted sources in our survey, perhaps because of its low credibility, it did not generate a demand for more information.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, they underscored that the messages relatives and other patients provided through the network represented significant emotional support 10 . In 2017, a nongovernmental organization that supplies patients in New Zealand with information on arthritis analyzed the features of the interactions through the Facebook page and identified that the comments were meant to seek and offer support, obtain information, or share experiences 21 . In line with these studies, although Facebook was among the most consulted sources in our survey, perhaps because of its low credibility, it did not generate a demand for more information.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, employees can be empowered to manage their own health with the help of professional guidance and peer-to-peer engagement on OHCs (Willis & Royne, 2017). The presence of a nurse moderator on OHCs was helpful for improving the content of the health information on online forums and also informing those who might be less likely to utilize in-person services (Grainger et al, 2017).…”
Section: Participatory Health Carementioning
confidence: 99%